Greed as the Root of Organized Crime: A Criminological Analysis of Fuel Adulteration Practices in the Oil and Gas Sector - Nisa Azkira (JUSTISI, 2026)
This study aims to analyze the practice of fuel adulteration as a form of organized economic crime that arises from social relationships and power structures within the management of the oil and gas sector. The research method employed is a normative legal approach, utilizing a literature review through the analysis of regulations, legal references, as well as criminological theory and moral philosophy. The novelty of this study lies in the reinterpretation of the concept of greed, which is not merely viewed as an individual psychological drive but also as a moral element that transforms into systemic crime through economic and political mechanisms. The findings of this study indicate that: (1) the practice of fuel adulteration reflects low moral integrity in the management of the oil and gas sector; (2) the existing oversight and law enforcement systems have failed to halt the chain of crime; and (3) this crime is systemic in nature because it is supported by a pattern of negligence and a structured network of interests. The study concludes that addressing fuel blending crimes requires an integrated approach that focuses not only on punishing perpetrators but also on structural reforms in legal governance and strengthening public ethics to prevent the recurrence of similar crimes.